Satisfacción familiar y depresión en adolescentes. Institución Educatica Antenor Orrego Espinoza. Distrito Laredo - Trujillo 2007 - Ganoza Guerrero, Gema Esmeralda (2008)
The present research is a descriptive study carried out in the “Antenor Orrego Espinoza Educational Institution” in order to determine the relation between family satisfaction and depression in teenagers. The sample was constituted by 214 teenagers who fulfilled the inclusion criteria: Regular presence in the time of performer, age between 15 and 17 years old, accept to participate volunteer in this research, to be situated in time, space and person. Para la recolección de datos se utilizó la escala de satisfacción familiar de David H. Olson y Marc Wilson y la escala de depresión Ivan K. Goldberg. In order to collect data, were used David H. Olson`s y Marc Wilson`s family satisfaction scale and Ivan K. Goldberg´s depression scale. The information got was processed and analyzed through the Chi- square statistical test. The following conclusions were reached after doing this research study:  The 74 percent of people presented no family satisfaction and the 25.2 percent showed family satisfaction.  The 50 percent showed slight or minor depression, followed by mild depression with 25 percent; possible minor depression: 10.7 percent; on the brink of the depression: 8.9 percent; the 2.8 percent with serious depression and the 1.9 percent presented unlikely depression.  The family satisfaction shows significant statistic relation to depression in teenagers (p<0.05).